2023
DOI: 10.1055/s-0043-1769584
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Emotional Intelligence, Self-Esteem, and Empathy among Nursing Students—A Pilot Study (Part 1)

Abstract: Objectives The aim of this study was to determine the relationship between emotional intelligence, self-esteem, and empathy of nursing students undergoing clinical experience in pediatric units. Materials and Methods A cross-sectional survey was conducted and data were gathered from 60 BSc nursing students undergoing clinical experience in pediatric units. Self-report questionnaires assessing emotional intelligence, self-esteem, and empathy were used and information about demographic details was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(41 reference statements)
2
1
0
Order By: Relevance
“…Nurses who used the emotion domain had comparable outcomes. Similar to our findings, Castelino and Mendonca (2023) reported an important positive association between EI and nursing students’ self-esteem. Similar results were reported in research conducted among 400 nursing students across four academic levels in Egypt ( r = 0.307, P < .001) ( Mohamed, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Nurses who used the emotion domain had comparable outcomes. Similar to our findings, Castelino and Mendonca (2023) reported an important positive association between EI and nursing students’ self-esteem. Similar results were reported in research conducted among 400 nursing students across four academic levels in Egypt ( r = 0.307, P < .001) ( Mohamed, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Previously, it was found that there is a significant relationship between EI and self-esteem among university students in Pakistan [13], which is similar to what was realized with student nurses participating in a crosssectional study in Saudi Arabia [14] aimed at determining their levels of emotional intelligence (EI) as well as self-esteem, and both were established to be high. Therefore, this finding demonstrates how complex an emotional intelligence construct can be within nursing students of middle-eastern universities, particularly when viewed against the backdrop of a specific cultural milieu such as the Saudi Arabian context.…”
Section: Introductionsupporting
confidence: 63%
“…20 Castellano PS et al in their study with nursing students in Mangalore, Karnataka found that a majority (65%) of the students had below average level of empathy. 21 Yucel H et al in their study on empathy in physiotherapy students in Istanbul found that the scores increased slightly after school entrance and the following years of study. However, they noted that there was a significant decrease in the clinical years.…”
Section: Discussionmentioning
confidence: 95%